Pengaruh Eksistensi Hutan Mangrove terhadap Aspek Sosial, Ekonomi dan Kearifan Lokal Masyarakat Pesisir di Desa Jaring Halus, Kecamatan Secanggang, Kabupaten Langkat - Adnin Musadri Asbi; Rahman Abdel Rauf (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Recognizing the importance of living needs derived from natural resources, a solution is needed to integrate ecological and economic aspects in order to work in balance. This research specifically examines the perspective of the people of Desa Jaring Halus in relation to the existence of mangrove forest ecosystem based on observation method. This study also analyzed the relationship of mangrove existence with social, economy and local wisdom of local community as well as looking for solution to increase income level of society by using questionnaire. The data derived from the questionnaire were analyzed descriptively quantitative. The results show that 92.85% of people feel the positive impact of maintained mangrove forest. The people of Jaring Halus Village have an unwritten local wisdom in managing and preserving mangrove forests to maintain social and economic sustainability. In order to increase the income level of the community, it is necessary to make a permanent mangrove nursery which is managed by the government performed by the community and marketed out of the village according to its allocation to increase household income by utilizing the development of Jaring Halus Village as Ecosystem Ecotourism Area.